A comparative evaluation of interleukin 1 beta and prostaglandin E2 with and without low-level laser therapy during En masse retraction - Jeffy Ann Jose; Sanju Somaiah; Sunil Muddaiah; Balakrishna Shetty; Goutham Reddy; S Roopa (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: Orthodontic forces are known to produce mechanical damage and inflammatory mediators such as prostaglandins (PGs) and interleukin (IL)-1, in the periodontium and dental pulp. Low-level laser therapy (LLLT) is a stimulator of the on-going biological process in tissue and found to be effective in modulating cell activity, which is involved in orthodontic tooth movement. Here, a humble effort has been made to study two such cytokines, namely IL-1 β and PG E2 (PGE2) which are partially responsible for bone turnover. The purpose of this study was to compare the changes occurring in the values of IL-1 β and PGE2 in the gingival crevicular fluid (GCF) during en masse retraction with and without LLLT. Methodology: GCF was collected using micropipettes from the distal ends of upper canines. The experimental side was exposed to biostimulation using 810 nm gallium-aluminum-arsenide diode laser and the contralateral side taken as control. A total of 10 irradiations for 10 s per site were given, five on the buccal side and five on the palatal side, to cover the entire periodontal fibers and the alveolar process around the tooth. After 7 days and 21 days of retraction, GCF sample was collected. Quantitative analysis of IL-1 β and PGE2 in the GCF samples was assessed using a commercially available Raybiotech® IL-1 β and Human PGE2. Results: (1) IL-1 β and PGE2 levels showed significant results from baseline to 21 days after LLLT irradiation. (2) LLLT-assisted retraction was significantly faster than conventional retraction. Interpretation and Conclusion: It was concluded from the study that IL-1 β and PGE2 levels peaked after LLLT. The difference in the levels of both cytokines was statistically significant.